The investigation of causes and influencing factors regarding non-reported medical errors among nurses working in hospitals in Zahedan - Mahdieh Sarhadi; Hojat Sheikhbardsiri; Razieh Sarhadi; Hosin Moine (Islamic Azad University, 2014)
Introduction: Medication errors are considered as important threatening challenges for health systems in all countries. They are also perceived as one of the most threatening factors for patient safety. Health education centers are intensively predisposed to a spectrum of medical errors occurrence due to students who learn in these centers. Therefore, this study was conducted to survey the reasons for not reporting errors regarding nursing students and nurses. Methods: In this descriptive-analytical comparative study 94 nursing students and nurses who worked in Khatamolanbia hospital of Zahedan participated in 2014. Data were collected using the questionnaire of not reporting medical errors. SPSS software was used for the analysis. Results: The results showed that the mean score for being afraid to report consequences, management factors reporting, and medication errors were (73.28±7.58), (14.30±3.38), and (8.63±2.49) for nursing students respectively, in addition, the scores of (34.9±9.84), (12.9±3.59), and (8.82±2.52) were obtained for nurses respectively. The results of parametric T-test regarding the two groups showed that there was a statistically significant difference between both groups (P≥0.05). Conclusion: Medical errors are considered as one of the most important issues in health care environments. So, the use of these methods depends on adopting a systematic approach to survey predisposition factors and removing them as well as designing a system to increase error reporting rate by nursing students and nurses to decrease and control such errors.